A role for tyrosine kinase activation in interleukin-1β induced nitric oxide production in the insulin producing cell line RINm-5F. Issue 1 (February 1994) - Welsh, Nils
Abstract : The aim of this investigation was to study the putative role of protein phosphorylation in interleukin-1β (IL-1β) induced signal transduction in insulin producing cells. For this purpose, insulin producing RINm-5F cells were exposed to IL-1β for 7 hours with or without different agonists and antagonists to protein kinases and phosphatases and the production of nitrite was subsequently determined. It has been shown earlier that IL-1β will stimulate the production of nitrite in such cells. It was found that EDTA, TPA and staurosporine did not affect IL-1β induced nitrite production. However, the tyrosine kinase antagonist tyrphostin inhibited, whereas sodium orthovanadate, okadaic acid and cyclosporin A, all inhibitors of protein phosphatases, potentiated IL-1β induced nitrite release to the medium. The tyrosine kinase antagonist genistein potentiated at a low concentration and inhibited at a high concentration the IL-1β effect. It is concluded that protein phosphorylation events, mediated either by protein kinases or phosphatases on both tyrosine and serine/threonine residues, may mediate or antagonize IL-1 induced signal transduction in insulin producing cells.